Transportation and The Use of Oxygen - Kun Arifi Abbas (Indonesian Journal of Anesthesiology and Reanimation, 2019)
Introduction: All living things need a certain amount of oxygen which is obtained from free air, which is continuous throughout life, but cannot be stored in the body as a reserve. Oxygen is distributed throughout the body to the mitochondria of cells which are used in metabolic processes along with glucose to produce ATP (energy source for cell activity) and remove carbon dioxide (CO2). Literature Review: The exchange of oxygen as a metabolic material for the body and carbon dioxide as the end product of the body's metabolism is done through a process called respiration. Blood pumped by the heart carries oxygen from the lungs to all body tissues and brings back the blood containing carbon dioxide from the tissues back to the lungs for gas exchange. Oxygen transport in the blood takes two forms, namely bound to hemoglobin/Hb (the largest) and dissolved. Meanwhile, the transportation of carbon dioxide in the blood takes 3 forms, namely:  carbonic ion (the largest), dissolved, and binds to Hb. Conclusion: The consumption of oxygen in the body requires processes and is associated with several organ systems. If one of the systems is not functioning properly, it can cause oxygen deficiency, thus the cells do not consume enough oxygen, which can cause anaerobic metabolism and if it becomes severe it will cause the death of cells, organs, and the individual.